2019 atomic spectrometry update – a review of advances in X-ray fluorescence spectrometry and its special applications. Issue 9 (10th July 2019) - Vanhoof, Christine; Bacon, Jeffrey R.; Ellis, Andrew T.; Fittschen, Ursula E. A.; Vincze, Laszlo
Abstract : This 2019 review covers developments in and applications of XRF techniques such as EDXRF, WDXRF, TXRF, XRF microscopy using technologies such as synchrotron sources, X-ray optics, X-ray tubes and detectors in laboratory, mobile and hand-held systems. Abstract : This review describes advances in the XRF group of techniques published approximately between April 2018 and March 2019. The review is selective with the aim of providing a critical insight into developments in instrumentation, methodologies and data handling that represent a significant advance in XRF spectrometry. It is not the intention of the review to cover comprehensively the applications of XRF techniques except in those cases where the non-destructive and remote sensing nature of XRF analysis makes it particularly valuable and the method of choice. These applications concern samples which are irreplaceable and of great cultural value such as works of art and archaeological artefacts.